2018
DOI: 10.18433/jpps30103
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Scientific Evolution of the Flavonoid Agathisflavone

Abstract: Purpose: Flavonoids are a group of secondary metabolites of the polyphenols class present in several plant species. Among them, the biflavonoid agathisflavone is of interest since it bears several biological effects that include: antiviral, antitumoral, antiprotozoal and neurogenic actions. In this sense, this study aims to use the important tool of scientific prospecting to assess the level of research development concerning the flavonoid agathisflavone. Methods: The experimental design was carried out throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Interestingly, a cytotoxic biflavonoid agathisflavone found in cashew nut ( Anacardium occidentale ) was shown to exhibit significant binding affinity with −8.0 kcal/mol against the SARS-CoV-2 M Pro ( Supplementary Table S3 ). Agathisflavone is a biflavanoid derived from plant source and has been found to possess several biological activities ( De Amorim et al, 2018 ). Various studies have found that agathisflavone possesses antioxidant, anti-inflammatory, antiviral, antiparasitic, cytotoxic, neuroprotective, and hepatoprotective activities.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a cytotoxic biflavonoid agathisflavone found in cashew nut ( Anacardium occidentale ) was shown to exhibit significant binding affinity with −8.0 kcal/mol against the SARS-CoV-2 M Pro ( Supplementary Table S3 ). Agathisflavone is a biflavanoid derived from plant source and has been found to possess several biological activities ( De Amorim et al, 2018 ). Various studies have found that agathisflavone possesses antioxidant, anti-inflammatory, antiviral, antiparasitic, cytotoxic, neuroprotective, and hepatoprotective activities.…”
Section: Resultsmentioning
confidence: 99%
“…Agathis avones have been reported for their cytotoxicity against malignant cell lines [23]. Agathis avone is a bi avanoid derived from plant source and has been found to possess several biological activities [24]. Various studies have found that agathis avone possesses antioxidant, anti-in ammatory, antiviral, antiparasitic, cytotoxic, neuroprotective, and hepatoprotective activities.…”
Section: Small Molecules/herbal Compounds Exhibiting Signi Cant Inhibmentioning
confidence: 99%
“…Agathisflavone ( Fig. 1; chemical formula: C 30 H 18 O 10 ; chemical name: 8-[5,7-dihydroxy-2-(4-hydroxyphenyl)-4-oxochromen-6-yl]-5,7-dihydroxy-2-(4-hydroxyphenyl)chromen-4-one; MW: 538.464 g/mol), a plant-derived biflavonoid, has been spotlight due to its diverse biological activities (6).…”
Section: Introductionmentioning
confidence: 99%